Teaching International Law in a Shifting Geopolitical Order: Implications for Social Justice Education - Lusha, Evelina; Velçani, Majlinda (European Journal of Social Science Education and Research, 2026)
This article examines how geopolitical shifts in public international law shape social justice education. Using document-based qualitative analysis across four illustrative domains: the United Nations (UN) response to Russia’s invasion of Ukraine, EU legal alignment in the Western Balkans, post-COVID-19 global health governance, and East Asian maritime disputes, the study develops a conceptual framework linking evolving legal norms to curriculum aims, pedagogy, and system supports. Findings indicate that while the language of international norms is clear due to treaties, resolutions, and adjudications, their implementation varies across actor constellations, institutional capacities, and degrees of political contestation. This model prescribes educational source-based inquiry, competency-aligned assessment, and partnerships drawing classrooms into the real legal-civic process when working where inclusion or equity and information integrity are matters of contestation. The research concludes with implementable steps towards infusing the elements of international law literacy into teaching and learning through participatory pedagogies founded on evidence-informed reasoning.